Enhancing Character Development Through Aqidah Akhlak Education in Islamic Elementary Schools: A Case Study from Central Java - Abu Dharin (AL-ISHLAH: Jurnal Pendidikan, 2025)
Aqidah Akhlak education is fundamental to character formation in students attending Islamic elementary schools. While character education has been widely studied, there is limited research examining the specific impact of Aqidah Akhlak education on students' moral development in Central Java, Indonesia. This qualitative study employed a case study approach to explore the role of Aqidah Akhlak education in shaping student character. Data were collected through direct observations and semi-structured interviews involving 16 teachers, 150 students, and 50 parents across Islamic elementary schools in the Cilacap, Banjarnegara, Banyumas, and Purbalingga regencies. The data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. Findings reveal that Aqidah Akhlak education contributes significantly to students' moral and social character, fostering traits such as honesty, discipline, and mutual respect. Additionally, the active involvement of parents and the surrounding community enhances the effectiveness of moral instruction in schools. The results suggest that Aqidah Akhlak instruction goes beyond religious doctrine, promoting a comprehensive moral framework for young learners. Collaborative efforts between educators, parents, and communities amplify its impact. Aqidah Akhlak education serves as a powerful strategy for character development in Islamic elementary schools. Future efforts should focus on curriculum integration and innovative pedagogical approaches to moral education at an early age.